New types of organic semiconductors based on diketopyrrolopyrroles and 2,1,3-benzochalcogenadiazoles: a computational study - Gogoi, Gautomi; Sahoo, Smruti R.; Rajbongshi, Basanta Kumar; Sahu, Sridhar; Sarma, Neelotpal Sen; Sharma, Sagar (Journal of molecular modeling, 2019)
A comprehensive computational study is performed on model compounds based on 2,1,3-benzochalcogenadiazoles and diketopyrrolopyrroles of A-π-A′-π-A architecture (A and A′ represent 2,1,3-benzochalcogenadiazoles and diketopyrrolopyrroles, respectively, and π is the bridging unit between them including thiophene, furan, and selenophene) for their utility as organic semiconductors. The compounds were found to possess planar geometry, which is a desired property for organic semiconductors. The electronic properties, including adiabatic and vertical electron affinity (EA), adiabatic and vertical ionization potential (IP), reorganization energy (λ), hole injection barrier and electron injection barrier, transfer integral, and charge mobility, were calculated. The electron affinity is higher in the case of thiophene/selenophene as the linker for a given terminal benzochalcogenadiazole than the corresponding compounds with furan as a linker, while the ionization potential is lowest for compounds having selenophene as the linker with a given terminal benzochalcogenadiazole moiety than the compounds having furan or thiophene as a linker. The hole injection barrier in these compounds is lower than the electron injection barrier, which facilitates the hole injection from the metal electrode, while hole reorganization energy is found to be larger than the electron reorganization energy. The compounds possess hole mobilities in the range of 2.50–4.91 cm 2 /Vs and electron mobilities in a similar range of 4.58–9.68 cm 2 /Vs. This study reveals that compounds based on a combination of diketopyrrolopyrrole and 2,1,3-benzochalcogenadiazole units would exhibit hole transporting properties and act as potential ambipolar materials.